Project-Based Learning and Ethno-STEM in Enhancing Science Literacy and Critical Thinking: A Systematic Review - Kurniawan, Wardi; Mahrus, Mahrus; Kosim, Kosim (Balai Publikasi Indonesia, 2025)
The purpose of this research is to examine the trend in the development of studies integrating the approaches of Project-Based Learning (PjBL) and EthnoSTEM to improve critical thinking skills and science literacy among students from 2016 to 2025. The issues identified in this research relate to the development of scientific publications that combine these three approaches and their contribution to enhancing skills relevant to the demands of the 21st century. The method applied is descriptive analysis with a bibliometric approach, using data obtained from Google Scholar, which was then analyzed using Publish or Perish (PoP) software and Dimensions.ai, and visualized using VOSviewer. The analysis results show a significant increase in publications addressing the theme of integrating PjBL, Ethno-STEM, science literacy, and critical thinking, especially after 2020, with the most dominant form of publication being book chapters. The keyword visualization confirms that the main focus of research in modern science education is geared towards the development of innovative learning models, improvement of critical thinking skills, and science literacy. Based on these findings, this research recommends further development of the integration of ethno-STEM and project-based approaches to support the quality of 21st-century learning